The association between non-depolarizing neuromuscular blockade agents and survival to discharge in dogs undergoing mechanical ventilation: a multi-center retrospective study of 227 dogs (2010–2020) - Ngo, Lena; Walton, Rebecca; Wolf, Jacob; Levy, Nyssa; Ludwik, Tasia; Thevelein, Britt; Blong, April; Cai, Jiazhang; Mochel, Jonathan (Frontiers in Veterinary Science, 2025)
ObjectiveTo evaluate the association between neuromuscular blockade agent (NMBA) use and outcome in dogs undergoing mechanical ventilation (MV), including survival to discharge, and complications.MethodsThe medical records for 227 mechanically ventilated dogs were reviewed for NMBA use, parameters of respiratory status (PaO2, PCO2, PF ratio, SpO2), MV settings, MV complications, and survival outcome.ResultsThe NMBA and non-NMBA groups included 28 and 199 dogs, respectively. The median partial pressures of oxygen in arterial blood (PaO2) in the NMBA and non-NMBA groups were 63 and 57 mmHg, respectively (P = 0.24). The median partial pressures of blood carbon dioxide levels were 58 and 51 mmHg, respectively (P = 0.07). The pulse oximetry percentage (SpO2) prior to initiation of MV were 88 and 94%, respectively (P = 0.02). The median PF ratios prior to MV were 90 and 215, respectively (P = 0.02). The median durations of MV were 18 and 24 h, respectively (P = 0.32). Eight (28.6%) dogs that received NMBAs survived to discharge, while 51 dogs (32.3%) that did not receive NMBAs survived to discharge (P = 0.87). Both PF ratio and SpO2 values were significantly lower in dogs that received NMBAs compared to dogs that did not (P = 0.02 and P = 0.02, respectively). There was no significant difference in tidal volume or peak inspiratory pressure at the time of MV initiation (P = 0.17 and P = 0.09, respectively). There was no significant difference between the incidence of complications in dogs that received NMBAs and those that did not (P = 0.08).ConclusionThis study revealed no statistical significance between NMBA use and survival or complications. However, dogs in the NMBA group likely had more severe hypoxemia than the non-NMBA group, as indicated by their lower PF ratios and SPO2 values prior to initiation of mechanical ventilation. The similarities in survival rate between the NMBA and non-NMBA patient populations, despite higher severity of respiratory pathology in the NMBA group, may suggest a potential therapeutic benefit to NMBA use for MV patients. Further investigation into the use of NMBAs in patients undergoing MV are warranted.